BRCA2 inhibition enhances cisplatin‐mediated alterations in tumor cell proliferation, metabolism, and metastasis. Issue 8 (6th June 2014) - Rytelewski, Mateusz; Tong, Jessica G.; Buensuceso, Adrian; Leong, Hon S.; Maleki Vareki, Saman; Figueredo, Rene; Di Cresce, Christine; Wu, Sherry Y.; Herbrich, Shelley M.; Baggerly, Keith A.; Romanow, Larissa; Shepherd, Trevor; et al.
Abstract : Tumor cells have unstable genomes relative to non‐tumor cells. Decreased DNA integrity resulting from tumor cell instability is important in generating favorable therapeutic indices, and intact DNA repair mediates resistance to therapy. Targeting DNA repair to promote the action of anti‐cancer agents is therefore an attractive therapeutic strategy. BRCA2 is involved in homologous recombination repair. BRCA2 defects increase cancer risk but, paradoxically, cancer patients with BRCA2 mutations have better survival rates. We queried TCGA data and found that BRCA2 alterations led to increased survival in patients with ovarian and endometrial cancer. We developed a BRCA2‐targeting second‐generation antisense oligonucleotide (ASO), which sensitized human lung, ovarian, and breast cancer cells to cisplatin by as much as 60%. BRCA2 ASO treatment overcame acquired cisplatin resistance in head and neck cancer cells, but induced minimal cisplatin sensitivity in non‐tumor cells. BRCA2 ASO plus cisplatin reduced respiration as an early event preceding cell death, concurrent with increased glucose uptake without a difference in glycolysis. BRCA2 ASO and cisplatin decreased metastatic frequency in vivo by 77%. These results implicate BRCA2 as a regulator of metastatic frequency and cellular metabolic response following cisplatin treatment. BRCA2 ASO, in combination with cisplatin, is a potential therapeutic anti‐cancer agent. Highlights: The anti‐proliferative effects of cisplatin are enhanced by BRCA2 inhibition. Non‐cancerous cells are not sensitized to cisplatin by BRCA2 inhibition. BRCA2 inhibition reverses acquired cisplatin resistance. The metabolic response to cisplatin is modulated by BRCA2. BRCA2 inhibition decreases tumor metastases in vivo following cisplatin treatment.